2015
DOI: 10.1002/pssa.201532350
|View full text |Cite
|
Sign up to set email alerts
|

Semipolar (112) InGaN light‐emitting diodes grown on chemically–mechanically polished GaN templates

Abstract: Abstractauthoren InGaN multiple quantum well light‐emitting diodes (LEDs) were grown on chemically–mechanically polished (112―2) GaN templates (up to 100 mm diameter wafers) by metalorganic vapour phase epitaxy. Initial GaN overgrowth on the polished templates in nitrogen ambient maintained the polished surface. The peak emission wavelength of the LEDs varied from 445 to 550 nm. In contrast to the simultaneously grown LEDs on as‐grown templates, the LEDs on polished templates have very smooth surface morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…56 Additionally, the rough surface morphology of the PSS-LED (Fig. 1) is another issue as it can cause nonuniform carrier distribution 21,44 and compositional fluctuations. 21 It has been previously found that polished PSS-GaN substrates can strongly enhance the luminescence uniformity of QWs and the performance of PSS-LEDs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…56 Additionally, the rough surface morphology of the PSS-LED (Fig. 1) is another issue as it can cause nonuniform carrier distribution 21,44 and compositional fluctuations. 21 It has been previously found that polished PSS-GaN substrates can strongly enhance the luminescence uniformity of QWs and the performance of PSS-LEDs.…”
Section: Discussionmentioning
confidence: 99%
“…1) is another issue as it can cause nonuniform carrier distribution 21,44 and compositional fluctuations. 21 It has been previously found that polished PSS-GaN substrates can strongly enhance the luminescence uniformity of QWs and the performance of PSS-LEDs. 21 The internal absorption has been found to be significant in nitrides for emission energy below the GaN band-edge due to background doping, leading to an increase in electronic transitions between donor-acceptor levels and structural defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations